Morfología floral en 20 árboles élite de la colección de cacao de la utmach - Feijoo Jaramillo, Karen Antonieta (Machala : Universidad Técnica de Machala, 2022)
Cocoa (Theobroma cacao) is native to the Ecuadorian Amazon jungle, in Ecuador there are 3 groups of known genotypes; criollos, forasteros y trinitarios, being the most important the Criollos for their export quality. The objective of this research was to characterize the morphology of cocoa flowers in 20 elite trees from the UTMACH collection. The work was carried out in the Plant Health Laboratory and the Santa Inés Farm in the cocoa area; 20 trees were selected from which 5 flowers of each were chosen to observe the floral structure and the pollen of each anther with the use of a binocular microscope, the variables analyzed were: diameter and area of ​​the pollen grain, length, width and color of the pedicel, length, width and color of the sepal, length of the petal, length, width and color of the staminoid, length and width of the stamen, length and width of the ovary. The results obtained indicate that the highest variance is distributed to five descriptors: AncE, Csep, AO, Lpet, Lest, according to the principal components analysis, the dendrogram and dispersion analysis. It is concluded that based on the floral morphology, six defined groups have been formed according to the five descriptors that explain 80.05% of the variance since the other nine descriptors do not present significance.
El cacao (Theobroma cacao) es originario de la selva amazónica Ecuatoriana, en Ecuador hay 3 grupos de genotipos conocidos; criollos, forasteros y trinitarios, siendo los más importantes los criollos por su calidad de exportación. El objetivo de esta investigación fue caracterizar la morfología de las flores de cacao en 20 árboles élite de la colección de la UTMACH. El trabajo se realizó en el laboratorio de Sanidad Vegetal y la Granja Santa Inés en el área de cacao; fueron seleccionados 20 árboles de los cuales se escogieron 5 flores de cada uno para observar la estructura floral y el polen de cada antera con el uso de un microscopio binocular, las variables analizadas fueron: diámetro y área del grano del polen, largo, ancho y color del pedicelo, largo, ancho y color del sépalo, largo del pétalo, largo, ancho y color del estaminoide, largo y ancho del estambre, largo y ancho del ovario. Los resultados obtenidos indican que la mayor varianza se distribuye a cinco descriptores: AncE, Csep, AO, Lpet, Lest, de acuerdo al análisis de componentes principales, el dendrograma y análisis de dispersión. Se concluye que basados en la morfología floral se han formado seis grupos definidos conforme a los cinco descriptores que explican el 80,05% de la varianza ya que los otros nueve descriptores no presentan significancia.
Keywords: GENOTIPO; CALIDAD DEL POLEN; INCOMPATIBILIDAD; BIOLOGÍA FLORAL